2004
DOI: 10.1016/j.bbamem.2004.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Applied field nonequilibrium molecular dynamics simulations of ion exit from a β-barrel model of the L-type calcium channel

Abstract: We present results of applied field nonequilibrium molecular dynamics simulations (AF NEMD) of a minimal beta-barrel model channel intended to represent an L-type calcium channel that suggests a possible relationship between glutamate side chain conformational changes and ion flux in calcium channels. The beta-barrel is used to provide a scaffolding for glutamate side chains and a confinement for electrolyte of dimensions similar to the expected channel structure. It was preloaded with ions to explore relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…32,34,63,64 Brownian dynamics simulations on this model indicate that Ca 2+ /Na + selectivity is governed solely by the electrostatic interactions inside the channel pore and not by the cation's excluded volume or the filter's structure and volume. 32,34,64 Lipkind and Fozzard 65 and Ramakrishnan et al 66 have explicitly modeled the Ca v channel's EEEE selectivity filter using the KcsA bacterial K + channel crystal structure and minimal β-barrel channel, respectively, as templates/scaffolds for anchoring the glutamates. Using molecular mechanics calculations with the consistent valence force field approximation, Lipkind and Fozzard 65 found that, in the absence of Ca 2+ , the selectivity filter forms a wide, open pore (∼6 Å) due to the repulsion among the negatively charged carboxylate groups lining the pore; upon Ca 2+ binding, all four Glu side chains move to the center of the pore and directly interact with a single dehydrated Ca 2+ .…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…32,34,63,64 Brownian dynamics simulations on this model indicate that Ca 2+ /Na + selectivity is governed solely by the electrostatic interactions inside the channel pore and not by the cation's excluded volume or the filter's structure and volume. 32,34,64 Lipkind and Fozzard 65 and Ramakrishnan et al 66 have explicitly modeled the Ca v channel's EEEE selectivity filter using the KcsA bacterial K + channel crystal structure and minimal β-barrel channel, respectively, as templates/scaffolds for anchoring the glutamates. Using molecular mechanics calculations with the consistent valence force field approximation, Lipkind and Fozzard 65 found that, in the absence of Ca 2+ , the selectivity filter forms a wide, open pore (∼6 Å) due to the repulsion among the negatively charged carboxylate groups lining the pore; upon Ca 2+ binding, all four Glu side chains move to the center of the pore and directly interact with a single dehydrated Ca 2+ .…”
Section: ■ Introductionmentioning
confidence: 99%
“…Using molecular mechanics calculations with the consistent valence force field approximation, Lipkind and Fozzard 65 found that, in the absence of Ca 2+ , the selectivity filter forms a wide, open pore (∼6 Å) due to the repulsion among the negatively charged carboxylate groups lining the pore; upon Ca 2+ binding, all four Glu side chains move to the center of the pore and directly interact with a single dehydrated Ca 2+ . 65 Using molecular dynamics simulations with explicit water molecules, Ramakrishnan et al 66 found that Ca 2+ was more effective than Na + in competing for the selectivity filter, thus highlighting the role of electrostatic forces in controlling the pore selectivity/ conductivity. 66 In contrast to the above calculations using classical force fields, we have treated the metal ions and carboxylate ligands in the EEEE selectivity filter explicitly using density functional theory (DFT) to account for electronic effects such as polarization of the participating entities and charge transfer from the carboxylates to the metal cation, which cannot be accurately treated using classical force fields; the rest of the pore was represented by a continuum dielectric.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with Monte Carlo [22,23,24,25] and molecular dynamics [19,20] simulations. In particular, with a model protein calcium channel, molecular dynamics simulations suggest [32] that when the channel is preloaded with two lateral calcium ions and one central sodium ion, one of the lateral Ca 2+ ions replaces the central Na + ion, typically forcing it out of the channel within 2 ns. This behavior is partially explained by the electrostatic results presented here, namely that the two-calcium state is more energetically favorable than the calcium-sodium-calcium state for all aspect ratios R/L greater than 0.1.…”
Section: Discussionmentioning
confidence: 99%
“…This is useful to develop qualitative and quantitative insights into the ion permeation mechanisms in this ion channel complex[ 19 22 ]. SMD is a popular approach that has been previously applied to study a number of ion channels, including KvAP voltage-gated potassium channel, voltage-gated sodium ion channel, calcium ion channels, mechanosensitive channels, etc [ 22 26 ].…”
Section: Introductionmentioning
confidence: 99%